Moving-Time and Moving-Ego Metaphors from a Translational and a Contrastive-Linguistic Perspective - Brdar, Mario; Brdar-Szabó, Rita (Research in Language, 2017)
This article is concerned with some cross-linguistic asymmetries in the use of two types of time metaphors, the Moving-Time and the Moving-Ego metaphor. The latter metaphor appears to be far less well-entrenched in languages such as Croatian or Hungarian, i.e. some of its lexicalizations are less natural than their alternatives based on the Moving-Time metaphor, while some others are, unlike their English models, downright unacceptable. It is argued that some of the differences can be related to the status of the fictive motion construction and some restrictions on the choice of verbs in that construction.